Coherent Quantum Emitters in Hexagonal Boron Nitride. Issue 9 (3rd August 2022) - Kubanek, Alexander
Abstract: Hexagonal boron nitride is an emerging 2D material with far‐reaching applications in fields like nanophotonics or nanomechanics. Its layered architecture plays a key role for new materials such as Van der Waals heterostructures. The layered structure has also unique implications for hosted, optically active defect centers. A very special type of defect center arises from the possibility to host mechanically isolated orbitals localized between the layers. The resulting absence of coupling to low‐frequency acoustic phonons turns out to be the essential element to protect the coherence of optical transitions from mechanical interactions with the environment. Consequently, the spectral transition linewidth remains unusually narrow even at room temperature, thus paving a new way toward coherent quantum optics under ambient conditions. In this review, the state‐of‐the‐art of defect centers in hexagonal boron nitride is summarized with a focus on optically coherent defect centers. The current understanding of the defect centers, remaining questions, and potential research directions to overcome pervasive challenges are discussed. The field is put into a broad perspective with impact on quantum technology such as quantum optics, quantum photonics, as well as spin optomechanics. Abstract : This review summarizes the state‐of‐the‐art of defect centers in hexagonal boron nitride with focus on optical coherence. The current understanding of the defect centers, remaining questions and potential research directions to overcome pervasive challenges are discussed. The topic is put into broad perspective with impact on quantum technology such as quantum optics, quantum photonics, and spin optomechanics.